1999
DOI: 10.1002/clc.4960221006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isosorbide dinitrate on electrocardiography, hemodynamics, and ventilation in patients with exercise‐induced elevation of pulmonary artery wedge pressure

Abstract: Isosorbide dinitrate treatment markedly improved exercise-induced left heart dysfunction, whereas excessive ventilatory response was unaffected, even after 3 h. Thus, measurements of the exercise hyperpnea did not properly reflect effective reduction of myocardial ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated a close association between exertional hyperpnoea and cardiac dysfunction ( Clark & Coats, 1994; Sullivan & Hawthorne, 1995; Jørgensen et al ., 1997 ; Jørgensen et al ., 1999 ). Accordingly, the fact that part of the excessive ventilatory response to exercise observed pre‐operatively persisted after elimination of the peripheral vascular insufficiency, was probably because the patients showed distinct evidence of left heart disease, with marked left ventricular dysfunction during moderate exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a close association between exertional hyperpnoea and cardiac dysfunction ( Clark & Coats, 1994; Sullivan & Hawthorne, 1995; Jørgensen et al ., 1997 ; Jørgensen et al ., 1999 ). Accordingly, the fact that part of the excessive ventilatory response to exercise observed pre‐operatively persisted after elimination of the peripheral vascular insufficiency, was probably because the patients showed distinct evidence of left heart disease, with marked left ventricular dysfunction during moderate exercise.…”
Section: Discussionmentioning
confidence: 99%